Estimation of Nasal Cavity and Conchae Volumes by Stereological Method - Emirzeoglu, M.; Sahin, B.; Celebi, M.; Uzun, Ali; Bilgic, S.; Tontus, H. O. (Via Medica, 2012)
Background: Studies evaluating the mean volumes of nasal cavity and concha are very rare. Since there is little date on the mentioned topic we aimed to carry out the presented study to obtain a volumetric index showing the relation between the nasal cavity and concha. Material and methods: The volumes of the nasal cavity and concha were measured in 30 males and 30 females (18-40 years old) on computed tomography images using stereological methods. Results: The mean volumes of nasal cavity, concha nasalis media, and concha nasalis inferior were 5.95 +/- 0.10 cm(3), 0.56 +/- 0.22 cm(3), and 1.45 +/- 0.68 cm(3); 7.01 +/- 0.18 cm(3), 0.67 +/- 0.31 cm(3) and 1.59 +/- 0.98 cm(3) in females and males, respectively. There were statistically significant differences in the volume of the nasal cavity and concha nasalis media (p < 0.05) between males and females, except for concha nasalis inferior (p > 0.05). Conclusions: Our results could provide volumetric indexes for the nasal cavity and concha, which could help the physician to manage surgical procedures related to the nasal cavity and concha. (Folia Morphol 2012; 71, 2: 105-108)
Tontus, H Omer/0000-0002-3435-9244; Sahin, Bunyamin/0000-0001-8538-8443;
Keywords: Stereology; Nasal Cavity; Volume